Digital Transformation in European Public Services
XIII, 234 p. 7 illus.
Keywords: This book examines digital transformation in the public sector. Drawing on case studies from around Europe, it identifies management practices that facilitate or hinder the implementation of digital transformation in various contexts and at different levels of government. Chapters consider how digital technologies are being used to improve public service delivery, how public institutions are employing AI, and the potential benefits for organizations and citizens. They also assess the obstacles to digital transformation, including budget constraints, legislation, and insufficient expertise. Providing nuanced insights from real-world projects that have sought to usher public sector institutions into the digital age, the book highlights what has worked well, what has not worked, and why. In doing so, it offers lessons for future projects and acts as a comprehensive guide offering actionable insights for academics and practitioners. It will appeal to all those interested in public administration, public management, and digital transformation. Nicolae Urs is Associate Professor and Vice-Dean at the College of Political, Administrative and Communication Sciences, Babeş-Bolyai University, Romania. David Špaček is Associate Professor at the Faculty of Economics and Administration, Masaryk University, Czech Republic. Steven Nõmmik is a Researcher at the School of Business and Governance, Tallinn University of Technology, Estonia.